Examining the Fraternal Birth Order Effect and Sexual Orientation: Insights from an East European Population - Fořt, Jakub; Kunc, Benjamin; Valentova, Jaroslava Varella; Bártová, Klára; Hudáčová, Kateřina (Archives of sexual behavior, 2024)
The development of human sexual orientation remains a complex and multifaceted subject. It is often studied but its origins continue to elude us. In this preregistered study, our primary objective was to demonstrate the fraternal birth order effect (FBOE), which assumes a higher prevalence of older brothers in gay men than in their straight counterparts and which has also been recently recorded in lesbian women. Our second aim was to explore any potential impact of the FBOE on anal-erotic role orientation (AERO), both in gay and straight men. Our study sample included 693 gay men, 843 straight men, 265 lesbian women, and 331 straight women from Czechia and Slovakia. Employing a conventionally parameterized logistic regression model, we substantiated the FBOE among both gay men (OR = 1.35 for maternal older brothers) and lesbian women (OR = 1.71). These outcomes were confirmed by a more nuanced parameterization recently proposed by Blanchard (2022). Nonmaternal older brothers did not exhibit a significant influence on their younger brothers' sexual orientation. Contrary to some earlier reports, however, our data did not establish the FBOE as exclusive to gay men with the receptive AERO. Furthermore, our observations indicated a lower offspring count for mothers of gay men compared to mothers of straight men. Emphasizing the positive FBOE outcomes, we acknowledge the need for caution regarding the various options that can be used to estimate the familial influences on sexual orientation.
Keywords: Young Adult; Homosexuality, Female; pořadí narození; Heterosexuality; sexuální a genderové menšiny; Male; Slovakia; Slovenská republika; mladý dospělý; homosexualita mužská; Česká republika; Male homosexuality; Siblings; Adult; dospělí; mužské pohlaví; Homosexuality, Male; Czech Republic; lidé; ženské pohlaví; Humans; homosexualita ženská; Birth Order; Birth order; Sexual Behavior; sexuální chování; Maternal fertility; Female homosexuality; sourozenci; heterosexualita; Female; Sexual orientation; lidé středního věku; Sexual and Gender Minorities; Middle Aged